The Effect of Experiential Marketing, Store Atsmosphere, Product Quality and Service Quality on Customer Satisfaction at Café Rosella - Khamdan Suriyok; Arif Syaifudin (Institute of Computer Science (IOCS), 2022)
Café Rosella is a cafe located in the city of Porong, Sidoarjo, which offers a unique concept and provides a variety of food and drinks suitable for students or people who are enjoying their time. However, there are some problems that are not considered, such as inadequate parking facilities, poor toilet cleanliness, loud music, unfriendly employee service, long employee service. The purpose of this study was to analyze the influence of Experiential Marketing, Store Atsmosphere, Product Quality and Service Quality on Consumer Satisfaction. This type of research is quantitative research. The method used in this research is purposive sampling by distributing questionnaires. Based on the results of the study, it shows that the independent variables, namely Experiential Marketing, Store Atmosphere, Product Quality and Service Quality, have a positive simultaneous effect on customer satisfaction. Partially, the Experiential Marketing variable has no effect on customer satisfaction. Store Atmosphere has a partial effect on consumer satisfaction. Product quality variable has a partial effect on consumer satisfaction. The service quality variable has a partial effect on customer satisfaction. Product quality variable has a partial effect on consumer satisfaction. The service quality variable has a partial effect on customer satisfaction. Product quality variable has a partial effect on consumer satisfaction. The service quality variable has a partial effect on customer satisfaction